2017
DOI: 10.1002/2017gl073430
|View full text |Cite
|
Sign up to set email alerts
|

Bounds on geologically current rates of motion of groups of hot spots

Abstract: It is widely believed that groups of hot spots in different regions of the world are in relative motion at rates of 10 to 30 mm a−1 or more. Here we present a new method for analyzing geologically current motion between groups of hot spots beneath different plates. In an inversion of 56 globally distributed, equally weighted trends of hot spot tracks, the dispersion is dominated by differences in trend between different plates rather than differences within plates. Nonetheless the rate of hot spot motion perpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(50 citation statements)
references
References 33 publications
(102 reference statements)
4
41
3
Order By: Relevance
“…Wang et al (2017) equally weighted all trends and thus did not consider the question of what are the most appropriate uncertainties to assign to hot spot trends. For the case in which it is assumed that errors between different hot spot tracks are uncorrelated, Wang et al (2017) found a global 1σ standard deviation, σ gl , of 23.1°. For the case in which it is assumed that errors between different hot spot tracks are uncorrelated, Wang et al (2017) found a global 1σ standard deviation, σ gl , of 23.1°.…”
Section: Dispersion Of Hot Spot Trends and Correlated Errorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Wang et al (2017) equally weighted all trends and thus did not consider the question of what are the most appropriate uncertainties to assign to hot spot trends. For the case in which it is assumed that errors between different hot spot tracks are uncorrelated, Wang et al (2017) found a global 1σ standard deviation, σ gl , of 23.1°. For the case in which it is assumed that errors between different hot spot tracks are uncorrelated, Wang et al (2017) found a global 1σ standard deviation, σ gl , of 23.1°.…”
Section: Dispersion Of Hot Spot Trends and Correlated Errorsmentioning
confidence: 99%
“…He postulated that plumes of hot rock rise up from deep in the mantle. Except for the work of Wang et al (2017), these prior studies have not resolved significant motion between hot spots. He used hot spot tracks, that is, chains of ancient volcanos leading to an active volcano, to estimate the geologically current motion of the plates relative to the deep mantle (Morgan, 1971).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The time dependence of mantle convection has also become clear. Richard Gordon and his colleagues (Wang et al 2017) have shown that the circulation is surprisingly steady, though major changes do occur from time to time when the lower boundary Gravity from DIR-R5 (wavelengths shorter than the 500 km removed) Gravity field for Africa from DIR-R5 filtered as in Figure 5c, whose boundary is shown by the black and yellow box. layer becomes unstable.…”
Section: Mantle Convectionmentioning
confidence: 99%